Globe trekker. Ultimate Middle East [videorecording (DVD)] : the complete Globe Trekker Middle East collection. - McCormick, Megan. (Megan Leah); Wright, Ian, 1965-; Morris, Holly, 1965- (Pilot Productions, 2012)
Travel through the Wadi Rum Desert and the ancient ruins of Petra, swim in the Dead Sea, see the oil fields of Kuwait, tee off at a desert golf course in Abu Dhabi, marvel at the awe inspiring structures of Dubai and discover a warm welcome in Beirut. Roving hosts Ian Wright, Megan McCormick, Zay Harding, and Holly Morris present the most interesting and exciting parts of the Middle East off the beaten tourist path.